Manliness - Mansfield, Harvey C., Jr., 1932- (Yale University Press, 2006)
This is the first comprehensive study of manliness, a quality both bad and good, mostly male, often intolerant, irrational, and ambitious. Our "gender-neutral society" does not like it but cannot get rid of it. Drawing from science, literature, and philosophy, Mansfield examines the layers of manliness, from vulgar aggression, to assertive manliness, to manliness as virtue, and to philosophical manliness. He shows that manliness seeks and welcomes drama, prefers times of war, conflict, and risk, and brings change or restores order at crucial moments. After a wide-ranging tour from stereotypes to Hemingway and Achilles, to Nietzsche, to feminism, and to Plato, the author returns to today's problem of "unemployed manliness." Formulating a reasoned defense of a quality hardly obedient to reason, he urges men, and especially women, to understand and accept manliness, and to give it honest and honorable employment.--From publisher description